Factors affecting the students' interest in attending school a qualitative study done in the University of Eastern Philippines. - Bayona, Anthony Julius Floralde; de Silva, Aracelli Anne Sarmiento (Anthony Julius Floralde Bayona and Aracelli Anne Sarmiento de Silva, 2005)
This study was made to look into the factors that affect the students' interest in atteding school. Specifically, it drew up the respondents' socio-demographic profile in terms of sex, age, family monthly income, birth order, household size, year level, hometown, and high school graduated from, the respondents' perception of attending school, and their motivation for attending school.